RELASI MITOS DAN PERSEPSI KHALAYAK PADA IKLAN YOUTUBE MOTOR HONDA BEAT DELUXE SMART KEY X KOBO KANAERU: THE RELATION BETWEEN MYTH AND PUBLIC PERCEPTION IN THE YOUTUBE COMMERCIAL FOR THE HONDA BEAT DELUXE SMART KEY X KOBO KANAERU MOTORCYCLE - Syarifah Arsitadewi Putri Gayanti; Wegig Murwonugroho; Agung Eko Budiwaspada (Universitas Trisakti, 2025)
The Relationship Between Myths and Public Perceptions in the Honda Beat Deluxe Smart Key x Kobo Kanaeru YouTube Advertisement. In recent years, advances in the digital era have given rise to a phenomenon of transformation in advertising in Indonesia. This study is motivated by the urgency to understand the impact of innovation in digital advertising strategies, particularly the potential use of Virtual YouTubers (VTuber) as a more efficient alternative to human models, in terms of cost, reduced risk of controversy, and message delivery effectiveness. However, the utilization of VTuber in the context of marketing in Indonesia remains suboptimal. Digital advertising transformation now enables advertisements to function not only as promotional media but also as a means of building narratives through myths, as seen in the use of VTuber as an advertising model. The Honda Beat Deluxe Smart Key x Kobo Kanaeru YouTube advertisement was selected as the focus of this research because it contains symbolic complexity and mythical construction that are intriguing and have not been extensively studied previously. This study aims to examine the relationship between the myths constructed in the advertisement and audience perception to understand the impact of this innovation on the potential for unique digital marketing communication strategies implemented by Honda. To achieve this objective, this study employs a qualitative descriptive method using Roland Barthes' semiotic analysis to identify the myths contained in the advertisement, as well as Schmitt's sociological theory approach to analyze how the audience interprets and responds to the message conveyed. Based on the discussion, it is found that myths in advertisements have a significant influence on how audiences understand messages, while also offering novelty in digital advertising creativity. The conclusion of this study emphasizes the close relationship between constructed myths and audience perception as an important element in digital advertising strategies.